Determination of Sulfite in some dried fruits using colorimetric method (Sebha University Conference Proceedings, 2024)
Sulfites are often used as preservatives in dried fruits to prevent discoloration and spoilage.  Some individuals may be sensitive or allergic to sulfites, and exposure can lead to adverse reactions.  Monitoring sulfite levels helps protect these consumers and allows researchers to evaluate the long-term health impacts of sulfite consumption and contribute to ongoing research in food safety.  The goal of the current study was to determine sulphur dioxide (SO2) concentration in some widely consumed dried fruits in Zawia city, Libya. Also is to ensuring that dried fruits are safe for consumption.   A nine dried fruit samples were randomly collected from local market in Zawia city, Libya.  The sulfur dioxide concentration in dried fruit samples were measured by colorimetric method using ONDA TOUCH UV-21 Spectrophotometer. The mean sulphite residue in apricot, white raisins, black raisins, banana, mango, kiwi, imported fig, local fig, plum was 252.2±2.50, 154.0±2.65, 166.0±1.00. 419.0±3.71. 223.2±2.37. 352.7±2.08, 259.7±2.52, 0, 326.9±7.34 respectively. The concentrations of SO2 in the studied samples were within the permissible limits according to FDA regulations (up to 2,000 ppm).  It appears that the content of this food preservative in dried fruits consumed in Libya has no serious risk for consumers in Libya.